Cognitive load and pedagogical tension in multi-platform online learning: Evidence from Chinese higher education - Xiaoqin Qiu; Nengsheng Qiu (PLoS ONE, 2026)
The proliferation of digital tools has transformed higher education into a complex, multi-platform online learning environment. This study investigates the paradoxical effects of this multi-platform environment on the student experience within Chinese higher education. Through the qualitative and quantitative data from a cross-sectional survey of 8,616 university students, we analyzed platform usage patterns, perceived benefits and challenges. The findings reveal a significant paradox: while students express positive attitudes towards platforms’ educational value, acknowledging benefits like enhanced self-directed learning and improved teacher-student interaction, they concurrently report substantial practical burdens. A serial mediation model confirmed that platform multiplicity increases extraneous cognitive load, which in turn elevates tool fatigue, ultimately leading to a more negative perception of the learning experience. This study identifies a core “pedagogical tension” between the intended benefits of educational technology and the lived reality of a fragmented, high-friction user experience that encourages instrumental engagement over deep learning. These findings underscore the urgent need for institutions and instructors to adopt a more strategic, integrated approach to educational technology to reduce fragmentation and prioritize a seamless student learning experience.